KEDUDUKAN ANAK ANGKAT DALAM KAJIAN HUKUM ISLAM DI INDONESIA - Safar Alim (Yayasan Baitul Hikmah al-Zain, 2025)
Adoption or also commonly called adoption is a form of legal actions that have important implications for some of the legal status of the parties involved in it. Assessment of the removal of the child is not found in some classical fiqh literature as a separate discussion, so as if the assessment on this matter is not so important-at least not in the classical fiqh codification. Referring to the actual conditions at this time, the institution of adoption is one of the institutions that need to be considered and given more attention, given the significant number of implications that can be caused. This study is a normative study of the laws and regulations of some countries is related with adoption. For the purpose of analysis is, the authors use the approach of socio-juridical and historical so hopefully will be able to describe the direction of the development of legal systems of some countries.